A low lymphocyte-to-monocyte ratio is an independent predictor of poorer survival and higher risk of histological transformation in follicular lymphoma. Issue 1 (2nd January 2021) - Mozas, Pablo; Rivero, Andrea; Rivas-Delgado, Alfredo; Nadeu, Ferran; Clot, Guillem; Correa, Juan Gonzalo; Castillo, Carlos; Bataller, Alex; Baumann, Tycho; Giné, Eva; Delgado, Julio; Villamor, Neus; et al.
Abstract: The lymphocyte-to-monocyte ratio (LMR) is a prognostic factor in different neoplasms, but its potential importance in follicular lymphoma (FL) is not well defined. We studied 384 FL patients for which the LMR was available at diagnosis. Baseline features and outcomes were compared between patients with an LMR ≤/>2.5. The 76 patients (20%) who had an LMR ≤2.5 were older and had a higher tumor burden. A low LMR was predictive of a lower 10-y progression-free survival (32 vs. 55%, p = .001) and overall survival (35 vs. 78%, p < .0001; HR = 2.3, p = .003 in a 6-element multivariable model). A low LMR was also an independent risk factor for histological transformation (11 vs. 6% at 10 years, p = .01). Likewise, patients with a low LMR had a higher rate of second malignancies. The potential utility of this widely available parameter and its contribution to well-established prognostic scores need to be explored in independent, prospective series.